1999
DOI: 10.1007/pl00007630
|View full text |Cite
|
Sign up to set email alerts
|

Dose Dependence and Time Course of Smoke Inhalation Injury in a Rabbit Model

Abstract: The dose dependence and time course of smoke inhalation injury were determined in a rabbit model. Animals were insufflated with 18-90 breaths of cotton smoke or room air (control) at a rate of 18 breaths/min and tidal volume of 12 ml/kg. Smoke-exposed animals exhibited dose-related histologic effects with progressive deterioration of respiratory function during the postexposure period of observation (96 h). The smoke-exposed rabbits had reproducible injuries to both airway mucosa and lung parenchyma, manifeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…In the current study, unbleached cotton was employed to determine if smoke altered injury compared to heated air alone. Unbleached cotton was selected to avoid chemical injury that might occur from toxic smoke, as in other smoke inhalation studies . Heavy metals or other toxins can further alter local tissue responses, and this toxic exposure would likely alter the healing outcomes in our model.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, unbleached cotton was employed to determine if smoke altered injury compared to heated air alone. Unbleached cotton was selected to avoid chemical injury that might occur from toxic smoke, as in other smoke inhalation studies . Heavy metals or other toxins can further alter local tissue responses, and this toxic exposure would likely alter the healing outcomes in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports from this and other laboratories have indicated that toxic smoke causes progressive injury to the airways, followed by injury to lung parenchyma (Barrow et al 1990; Traber and Herndon 1991; Bidani et al 1999; Dost 1991). Even though rapid release of chemical mediators in the airways has been suggested as a mechanism for injury, there is limited understanding of the underlying processes…”
Section: Discussionmentioning
confidence: 71%
“…Previous reports from this and other laboratories have indicated that toxic smoke causes progressive injury to the airways, followed by injury to lung parenchyma (Barrow et al 1990; Traber and Herndon 1991; Bidani et al 1999; Dost 1991). Even though rapid release of chemical mediators in the airways is a suggested mechanism for injury, there is limited understanding of the underlying processes that lead to delayed parenchymal injury.…”
Section: Discussionmentioning
confidence: 71%